Dislipidemia em escolares na rede privada de Belém - RIBAS, Simone Augusta (Sociedade Brasileira de Cardiologia, 2019)
Background: Currently, childhood dyslipidemia, associated to other non-transmissible diseases such as diabetes, hypertension and obesity, represent a significant public health problem in Brazil. Objective: To investigate the prevalence of dyslipidemia in children and adolescents from private schools in the city of Belem, state of Para, Brazil. Methods: Transversal and prospective study that assessed 437 schoolchildren, paired by sex. The age range was established between 6 and 19 years of age and stratified in four subgroups (6 to 9 years; 10 to 12 years; 13 to 15 years and 16 to 19 years). To obtain the anthropometric variables, weight and height were measured for the calculation of the body mass index and skin folds were measured for the calculation of body fat percentage. The serum lipoprotein profile was obtained through the measurement of total cholesterol, triglycerides, LDL-cholesterol and HDL-cholesterol after a 12-hour fasting period, by enzymatic methods. Results: Of the total number of schoolchildren analyzed, 126 (28.8%) were overweight and 158 (36.2%) presented a high adiposity index. The children (33.6%) presented a higher prevalence of obesity when compared to the adolescents (10.1%; p < 0.001). Regarding the biochemical characteristics, it was observed that 214 (41%) presented some alteration in the lipid profile and that children and adolescents in the age range of 10 to 15 years were the age groups that presented the highest rates of dyslipidemia (34.6% and 25.5%), respectively. Conclusion: These findings demonstrate the importance of establishing an early diagnosis of the lipid profile, mainly if it is already associated to another risk factor, such as obesity. (Arq Bras Cardiol 2009; 92(6) : 412-417).